Commune, Popolo and food shortages at Perugia (1257-1260) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The rise to power of the Popolo at Perugia can be revisited by focusing on the effects of the volcanic eruption of Samalas, mostly on the food supply. Between 1257 and 1260 Perugia was hit by a succession of food shortages and found it very difficult to raise grain and foodstuff in general. The food supply became one of the main goals of the Popolo’s policy, stimulating debates in the local council and causing the creation of new fiscal instruments and new institutions to control the grain market. The analysis of the judicial records has made it possible to point out the increase of the punishment of agricultural crimes, thus providing another perspective to understand the crisis.
Keywords: Perugia; Popolo; food crisis; taxation; agricultural crimes; justice